2005
DOI: 10.2174/1568007053544183
|View full text |Cite
|
Sign up to set email alerts
|

NMDA/NR2B Selective Antagonists in the Treatment of Ischemic Brain Injury

Abstract: Glutamate is the main excitatory neurotransmitter in the central nervous system and it plays a significant role not only in synaptic transmission but also in acute and chronic neuropathologies including stroke. Presently, four receptors for glutamate have been identified and the NMDA receptor family is the most intensively studied. A number of NMDA receptor antagonists have been developed and used for treatment of neurological diseases in patients. However, all of these drugs have been failed in clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 47 publications
2
41
0
1
Order By: Relevance
“…The NMDA receptor is strongly implicated in this acute neurotoxicity, and NMDA receptor antagonists targeted at the glutamate binding site, the glycine binding site, the channel pore, and an allosteric site on the GluN2B subunit are all neuroprotective in multiple preclinical models (Green, 2002;Parsons et al, 2002;Lo et al, 2003;Hoyte et al, 2004;Small and Tauskela, 2005;Wang and Shuaib, 2005;Muir, 2006). These data supported the clinical investigation for utility in preventing death and long term disability after stroke and TBI in man.…”
Section: A Glutamate Receptor Antagonists and The Prevention Of Acutmentioning
confidence: 87%
“…The NMDA receptor is strongly implicated in this acute neurotoxicity, and NMDA receptor antagonists targeted at the glutamate binding site, the glycine binding site, the channel pore, and an allosteric site on the GluN2B subunit are all neuroprotective in multiple preclinical models (Green, 2002;Parsons et al, 2002;Lo et al, 2003;Hoyte et al, 2004;Small and Tauskela, 2005;Wang and Shuaib, 2005;Muir, 2006). These data supported the clinical investigation for utility in preventing death and long term disability after stroke and TBI in man.…”
Section: A Glutamate Receptor Antagonists and The Prevention Of Acutmentioning
confidence: 87%
“…15 However, although glutamate-induced excitotoxicity is a crucial component of the initial ischemic insult, all tested antiglutamatergic drugs have failed in clinical trials. 2 One of the reasons for this failure might be the rapid and early Figure 2. CTX reperfusion group showed the reduced initial neurological deficit and the enhanced functional recovery over a 5-week period (A).…”
Section: Discussionmentioning
confidence: 99%
“…C ell death after cerebral ischemic insult can be induced in 3 ways: (1) by excitation (excitotoxicity), (2) by oxidative stress with free radicals, and (3) by apoptosis. 1 When the brain fails to generate sufficient ATP and this results in energy failure, ionic gradients are lost.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After this finding, ifenprodil has been used in an exceptionally wide range of studies to explore the role of GluN2B-containing NMDA receptors in development, normal brain function, and disease (reviewed by Mony et al, 2009a). These studies have identified a wide range of normal processes and neurological diseases that involve GluN2B receptors (Wang and Shuaib, 2005;Mony et al, 2009a;Traynelis et al, 2010) and have stimulated a vigorous medicinal chemistry effort that has led to the identification of a large family of diverse organic molecules that can selectively inhibit GluN2B receptors (Table 1 and Fig. 5).…”
Section: The Glun2b Amino-terminal Domain Harbors a Binding Site For mentioning
confidence: 99%